THE ANALYSIS OF DOMESTICATION AND FOREIGNIZATION STRATEGIES IN RENDERING CULTURE SPECIFIC ITEMS IN ANDREA HIRATA担 LASKAR PELANGI - Sry Utamy Lestarie, - (2011)
The paper entitled The Analysis of Domestication and Foreignization Strategies in Rendering Culture Specific Items in Andrea Hirata's Laskar Pelangi novel examines the occurrence of culture-specific items (CSIs) in Laskar Pelangi according to Newmark (1988), also seeks the preferable translation strategy between domestication and foreignization in rendering those CSIs according to Venuti (1995) and measures the accuracy level based on Waddington's Method A (2001) and Larson's theory of accuracy (1984). The data of this research are in form of words or idioms containing culture specific items. By using descriptive approach, they are analyzed and classified into categories of CSIs and after that divided into domestication and foreignization strategies. To find the accuracy level, each of culture specific items is also classified into the accuracy levels. The findings show that there are eleven categories found in the novel with total 336 items. Those eleven categories are dialect (0,30%), gestures and habits (0,30%), measuring system (0,30%), organization, customs, activities, procedures, concepts (4,76%), social system (5,06%), techno-economic system (6,85%), social culture (11,01%), toponym (11,90%), material culture (12,80%), ecology (20,54%), and ideational system (26,19 %). Other findings reveal that domestication is more preferred in rendering culture specific items in the novel into English. As many as 63,10% of CSIs are domesticated while the rest 36,90% are foreignized. It proves that western culture still dominates source cultural values and thus leads the translator to adjust the translation for the sake of target readers' convenience by risking the cultural values lied in original text. The preferable strategy also affects the accuracy level as the omission level becomes the biggest accuracy level in this translation with total of 37%. It is followed by accurate level (27%), nonsens (14%), addition (10%), loss of meaning (9%), contresens (1%), fauxsens (1%), and unresolved extralinguistic references (1%). However, as a whole both domestication and foreignization contribute to the accuracy of translation since both strategies can stand on the same accuracy level.